Keterbukaan Informasi Publik dan Kebebasan Pers dalam Konteks Reformasi Birokrasi - Nanang Rustandi (STISIP Widyapuri Mandiri Sukabumi, 2022)
Freedom of the press guarantees that the government and the public are aware of the various realities that are happening or the opinions, views, of experts on an issue and conflict. While the KIP Law has an important role in changing the paradigm of society, which initially believed that public bodies were obliged to report accountability, since the KIP Law was enacted, the public has the right to obtain the information they need, and has the right to demand that public bodies publish such information. This study aims to determine the role of the UU KIP in promoting press freedom, and the role of press freedom in realizing bureaucratic reform. This research uses a qualitative descriptive methodology to explain phenomena and to find knowledge or theories about research at a certain time. The technique of collecting data is through library research, which is a way of collecting data by referring to books or scientific documents, literature, notes, and various reports that have been available as references to obtain data on the problem being studied. The results of the study show that the universal principle of openness to public information places press freedom as part of the scope of freedom of information. Achieving the true goal of information disclosure requires a press climate that is free, independent and professional. Meanwhile, the presence of the Law on the Disclosure of Public Information is expected to support the implementation of the press's function so that public bodies are obliged to open the tap of information through all available channels. The press has the right to seek, obtain and disseminate ideas and information, and public participation can be carried out by carrying out activities to develop press freedom and promote press freedom. guarantee the right to obtain the necessary information. Thus, public information disclosure and press freedom are two things that are bound and mutually reinforcing in an effort to realize transparent and accountable governance as a manifestation of bureaucratic reform that is currently underway.